Learning hope: an epistemology of possibility for advanced capitalist society - Amsler, Sarah (Palgrave Macmillan, 2016)
Drawing on the critical theories of Ernst Bloch and Boaventura de Sousa Santos, as well as on the knowledge and learning practices of counter-capitalist social movements, Amsler’s chapter offers a reading of political hopelessness amongst educators in England through a critical epistemology which discloses it as ‘unfinished’ and potent material within a global politics of possibility. She invokes methods from Bloch’s critical process-philosophy of ‘learning hope’ which allows for three reality-shifting operations: (1) the making of distinctions between what is ‘not’, ‘not-yet’ and ‘nothing’ in experience and historical process; (2) identifying and creating ‘fronts’ of possibility for mediating reality in concretely utopian ways; and (3) the recognition of a multiplicity of anti-hegemonic scales and modes of transformation, and explains why these matter in movements not just for social change but for the immanent creation of an other reality.